Unveiling the Dynamics of Ethiopian Defence Diplomacy: A Focus on Peacekeeping Contributions - Sigatu, Kaleab Tadesse (European Scientific Journal, ESJ, 2023)
This paper addresses Ethiopia’s defence diplomacy mainly through its participation in peace support operations. This qualitative research study aims to analyze and synthesize the findings from relevant literature reviews, with the objective of essentially to show to what extent Ethiopia has used peacekeeping participation as a tool of defence diplomacy in contributing to peace and security especially in the Horn of Africa region. The paper finds out Ethiopian defence diplomacy is an important tool for Ethiopia to achieve its foreign policy objectives globally, to promote regional stability and cooperation, in addition to as a means for seeking regional influence.